Evaluation of the Use of Akin (Sandıklı/Afyonkarahisar) Basalts as Railway Ballast - Kozak, Mehmet (Fırat University, 2025)
The aim of this study is to evaluate the use of Akin (Sandıklı/Afyonkarahisar) basalts as railway ballast. Investigations were carried out in the basalt quarry and samples were taken for the experiments to be carried out in the study. According to the Ballast Technical Specification, abrasion resistance determination with Micro-Deval, resistance to fragmentation with Los Angeles test, Magnesium Sulphate test, water absorption and grain density tests were carried out to determine the physical properties of the rock. Petrographic analysis was carried out to determine the name and origin of the rock. The rock's resistance to abrasion was determined as 6%, resistance to fragmentation as 9%, frost resistance value as 1%, grain density as 2.90 Mg/m3 and water absorption rate as 0.3%. The experimental studies have shown that Akin (Sandıklı/Afyonkarahisar) basalts can be used as railway ballast in conventional railway, speed train and high-speed train lines. It will provide an idea about the usability of Akin (Sandıklı/Afyonkarahisar) basalt quarry in meeting the ballast needs of Ankara-İzmir high-speed train lines, which are currently under construction, and Eskişehir-Antalya high-speed train lines, which are currently under project studies.

Bu çalışma ile Akin (Sandıklı/Afyonkarahisar) bazaltlarının demiryolu balastı olarak kullanımının değerlendirilmesi amaçlanmıştır. Bazalt ocağında incelemeler yapılarak çalışmada yapılacak deneyler için örnekler alınmıştır. Balast Teknik Şartnamesine göre kayacın fiziksel özelliklerin belirlenmesi için Mikro – Deval ile aşınma direnci tayini, Los Angeles deneyi ile parçalanmaya karşı direnç tayini, Magnezyum Sülfat deneyi, su emme ve tane yoğunluğu deneyleri yapılmıştır. Kayacın isim ve kökenini belirlemek için petrografik analiz yapılmıştır. Kayacın aşınmaya karşı direnci % 6, parçalanmaya karşı direnci % 9, dona dayanıklılık değeri % 1, tane yoğunluğu ise 2,90 Mg/m3, su emme oranı ise % 0,3 olarak tespit edilmiştir. Yapılan deneysel çalışmalar konvansiyonel demiryolu, hızlı tren ve yüksek hızlı tren hatlarında Akin (Sandıklı/Afyonkarahisar) bazaltlarının demiryolu balastı olarak değerlendirilebileceğini göstermiştir. Akin (Sandıklı/Afyonkarahisar) bazalt ocağının, yapımı devam eden Ankara-İzmir, proje çalışmaları devam eden Eskişehir-Antalya yüksek hızlı tren hatların balast ihtiyacının karşılanmasında kullanılabilirliği hakkında fikir verecektir.
Akin (Sandıklı/Afyonkarahisar) Bazaltlarının Demiryolu Balastı Olarak Kullanımının Değerlendirilmesi
Keywords: Transportation Engineering; Ulaştırma Mühendisliği; Construction Materials; Yapı Malzemeleri; Applied Geology; Uygulamalı Jeoloji